2014
DOI: 10.1111/ejh.12242
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for pulmonary hypertension in patients with hemoglobin E/β‐thalassemia disease

Abstract: Prevalence of PHT in E/β-Thal patients was 37.3% without gender preponderance. Those with severe hemolysis and asplenia invariably had severer PHT. Strong risk factors were asplenia and associated markedly elevated values of sVCAM-1, cell-free Hb, and NRBCs in blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
11
1
1
Order By: Relevance
“…A recent multicenter Italian study reported TRV>3.0 m/s in 5.7% and RHC confirmed pulmonary hypertension in 2.1% [31]. However, the prevalence of pulmonary hypertension varies significantly with genotype [32] and [33] and our study cohort was much more ethnically and genetically diverse than the Italian studies. Previous reports from a large American cohort suggested TRV > 2.5 m/s in 33% of patients and TRV > 3 m/s in 5% [17].…”
Section: Discussionmentioning
confidence: 68%
“…A recent multicenter Italian study reported TRV>3.0 m/s in 5.7% and RHC confirmed pulmonary hypertension in 2.1% [31]. However, the prevalence of pulmonary hypertension varies significantly with genotype [32] and [33] and our study cohort was much more ethnically and genetically diverse than the Italian studies. Previous reports from a large American cohort suggested TRV > 2.5 m/s in 33% of patients and TRV > 3 m/s in 5% [17].…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, cell-free hemoglobin can activate platelets through the action of adenosine diphosphate-bound hemoglobin (79). Chronic platelet activation may, in part, contribute to an increased frequency of vascular complications in thalassemia such as pulmonary hypertension (3,11), pulmonary embolism (173), cerebral thrombosis (209), and peripheral arterial and venous thrombosis (22,30). Prevention of thrombosis, particularly FIG.…”
Section: Fig 2 Hbe Acts As a Bmentioning
confidence: 99%
“…World Health Organization (WHO) group IV pulmonary hypertension and WHO group I pulmonary hypertension (pulmonary arterial hypertension, PAH) have been demonstrated in patients who have undergone splenectomy for pyruvate kinase deficiency, stomatocytosis, hereditary spherocytosis, unstable hemoglobinopathies, paroxysmal nocturnal hemoglobinuria, myeloid metaplasia, thalassemia, Gaucher disease, trauma, and nonhemolytic conditions, as well as in a case of congenital asplenia (13,15,21,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Association Of Splenectomy With Pulmonary Hypertensionmentioning
confidence: 99%